Att bevisa målbildsuppsåt vid penningtvättsbrott – möjligheter och svårigheter - Karkkulainen, Jussi (Nordisk Tidsskrift for Kriminalvidenskab, 2024)
Abstract Proving target intent in money laundering cases: possibilities and problems. Many criminal law researchers have stated that the volition of the perpetrator is relevant only when their purpose is a consequence that forms a part of the constituent elements of a criminal offence. Hence, the perpetrator could not have the other constituent elements of a criminal offence, e.g. circumstances, as their purpose or target. However, it has been recently stated in legal literature that the circumstances that form part of the constituent elements of an offence may also be relevant as targets of the offender. This form of criminal intent has been designated target intent (dolus propositum), where the offender at the time of the criminal act considers the circumstance element of a criminal offence their target. The current paper concentrates on target intent in money laundering, where the offender must have criminal intent in relation to the fact that the property they, e.g., receive, use, convert, convey, transfer, transmit or possess has been obtained through an offence. The paper examines whether the Finnish lower court cases concerning money laundering contain facts that could work as evidence of target intent on the part of the offender. It also considers the type of problems that can arise when attempting to prove target intent in money laundering cases. The study applies qualitative content analysis within a theory-oriented approach as its main methodology. The theory of target intent with its six subcategories – causing intent, selecting intent, ensuring intent, strengthening intent, revealing intent and desiring intent – provide a theoretical framework for the content analysis. These six subcategories represent the manifestations of target intent on a theoretical level. Most importantly, the subcategories structure the external and objectively observable facts by which the offender may express his or her will. The subcategories of target intent should therefore be utilised when assessing the possibility of target intent. By referring to these subcategories, it is possible to assess whether the offender has acted with target intent at trial. The analysis concludes that it is difficult to prove target intent in money laundering cases. Proving target intent in particular demands details concerning the behaviour of the perpetrator at the time of the criminal act. From the standpoint of the criminal law, intent cannot be based on thoughts and attitudes that have nothing to do with actual conduct of the offender. Hence, target intent must be apparent at the time of the offence and appear in the act in question. Money laundering is typically a drawn-out process as opposed to a spontaneous crime. This makes it challenging to recognise whether the offender has, at a certain moment, considered the definitional circumstance of his or her target. Moreover, the money launderer seldom indicates their willingness to handle only funds derived from criminal activities in an unequivocal way. Based on the analysis, target intent mainly arises in criminal cases where the offender has also been aware of the existence of the relevant circumstance. This poses a significant challenge for target intent in money laundering cases where proving intent seems to be difficult in general. Instead of visibly showing that they are searching for property obtained through an offence, the money launderer rather wilfully avoids information concerning any illicit origins.